Об эквивалентности вероятностных мер, порожденных решениями нелинейных эволюционных дифференциальных уравнений в гильбертовом пространстве, возмущенных гауссовскими процессами. I - Фомин-Шаташвили, А.А.; Фомина, Т.А.; Шаташвили, А.Д. (Кибернетика и системный анализ, 2011)
В абстрактному гільбертовому просторі Нрозглянуто нелінійні еволюційні диференційні рівняння з необмеженими лінійними операторами збурення гаусівськими випадковими процесами. Для задачі Коші диференціальних рівнянь доведено достатні умови існування і єдиності їх розв’язків, а також достатні умови еквівалентності ймовірнісних мір, породжених цими розв’язками. В явному вигляді обчислено відповідні щільності Радона–Нікодима у термінах коефіцієнтів або характеристик розглянутих диференціальних рівнянь. Nonlinear evolutionary differential equations with unbounded linear operators, disturbed by Gaussian random processes, are considered in an abstract Hilbert space. For the Cauchy problem of the differential equations under study, the sufficient existence and uniqueness conditions for their solutions and the sufficient conditions for the equivalence of the probability measures generated by these solutions are derived. Moreover, the corresponding Radon–Nikodym densities are calculated explicitly in terms of the coefficients or characteristics of the considered differential equations. Refs: 49 titles.